Analisis Kualitas Jaringan Akses Tembaga Terhadap Layanan Speedy Studi Kasus Di PT.Telkom,Tbk Divisi Access Site Operation Purwokerto - Wahyu Pamungkas; Nunung Sadtomo; Erlinda Febrianingtyas (JURNAL INFOTEL, 2012)
The development of fast evolving telecomunication technologies starting from communications cable to wireless communications. One of the communication cable for data is a technology Asymetric Digital Subscriber Line (ADSL). ADSL technology is an access technology that enable data communications, voice and video simultaneously at cooper access network media. Speedy service is one example of the use of ADSL technology. Telkom Speedy offers internet access speeds ranging from 384 Kbps for downstream speed and 3 Mbps for upstream speed. Speed of access internet is affected by the quality of the network. Parameters that effect the quality of network are : attenuation, Signal to Noise Ratio (SNR), Packet Loss, Bit Error Ratio (BER), jitter and time to life (TTL). In this study analysis of network quality affected by these parameters were measured advance to the quality of the network by using the EMBASSY software, while the perform measurements speedtest by using internal web aplications PT.Telkom,Tbk. After measurement is complete then performed the analysis for determine network quality. Based on observations can be known on the upload and download speed the capacity of 384 Kbps, 1024 Kbps and 3 Mbps. Of these three on capacity can be known to the average percentage of the upload speed is found to be 83,33 %, while the percentage of download speeds is found to be 76,67 %